2013
DOI: 10.1093/humrep/det022
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptional low-dose aspirin for the prevention of hypertensive pregnancy complications and preterm delivery after IVF: a meta-analysis with individual patient data

Abstract: Based on the current meta-analysis with IPD we found no confirmation for the hypothesis that preconceptionally started low-dose aspirin reduces the incidence of hypertensive pregnancy complications or preterm delivery in IVF women. Larger studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Some authors such as Han et al and Beigi et al are of the conviction that anti-inflammatory treatments and anticoagulation treatments are good to use [21,22]. Whereas the utter conviction the other authors like Groeneveld et al [23] is that such treatments are not effective for pregnancy complications like preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors such as Han et al and Beigi et al are of the conviction that anti-inflammatory treatments and anticoagulation treatments are good to use [21,22]. Whereas the utter conviction the other authors like Groeneveld et al [23] is that such treatments are not effective for pregnancy complications like preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…Data concerning the use of aspirin for preventing hypertensive disorders in pregnancy are controversial as well. A RCT found such a benefit in the use of aspirin for the prevention of hypertensive complications of pregnancy [25], however, a recent meta-analysis with individual patient data did not recommend the low-dose aspirin for hypertensive complications and preterm delivery after IVF [26]. One study found low incidence of ovarian hyperstimulation syndrome in patients receiving low-dose aspirin [27].…”
Section: Low-dose Aspirinmentioning
confidence: 99%
“…The ratio between the prostaglandins thromboxane and prostacyclin modulates vascular blood flow, with thromboxane A 2 acting as a vasoconstrictor and promoting platelet aggregation, while prostacyclin acts as a vasodilator and inhibits aggregation. Increased thromboxane and reduced prostacyclin levels are associated with infarction and thrombotic vasculopathy, which are well-known features in preeclamptic placentas [22]. …”
Section: Pathogenesismentioning
confidence: 99%
“…And, unlike high-dose NSAIDs, low-dose aspirin does not appear to increase the risk for ductus arteriosus closure in utero [45]. Analysis for preconceptional low-dose aspirin administration for prevention of preeclampsia after in vitro fertilization (IVF) found no significant reduction of hypertensive pregnancy complications compared to placebo group [22]. …”
Section: Clinical Trials Of Low-dose Aspirin Administration For Prmentioning
confidence: 99%